Imagining karma : ethical transformation in Amerindian, Buddhist, and Greek rebirth - Obeyesekere, Gananath (University of California Press, 2002)
With 'Imagining Karma', Gananath Obeyesekere embarks on the comparison of rebirth concepts across a wide range of cultures. The book makes a case for disciplined comparison, a humane view of human nature, and a theoretical understanding of 'family resemblances' and differences across great cultural divides.
Keywords: Reincarnation -- Buddhism.; Reincarnation -- Comparative studies.; Religious ethics -- Comparative studies.; Réincarnation -- Bouddhisme.; Réincarnation -- Études comparatives.; Morale religieuse -- Études comparatives.; RELIGION -- Comparative Religion.; RELIGION -- Buddhism -- General.; Reincarnation; Reincarnation -- Buddhism; Religious ethics; Reïncarnatie.; Vergelijkend onderzoek.; amerindian tradition.; buddhism.; buddhist tradition.; canada.; classicists.; cosmology.; cross cultural scholarship.; cultural relativism.; cultural stories.; death.; empedocles.; ethics.; greek tradition.; human condition.; indic civilizations.; indologists.; intellectual context.; karma.; melanesia.; methodological framework.; nietzsche.; personal transformation.; philosophy.; pindar.; plato.; pythagoras.; rebirth.; reincarnation.; siberia.; textbooks.; weber.; west africa.; wittgenstein.; Comparative studies